ENT and mucopolysaccharidoses - Pier Marco Bianchi; Renato Gaini; Silvano Vitale (BMC, 2018)
Abstract The mucopolysaccharidoses (MPS) are a heterogeneous group of inherited metabolic disorders, each associated with a deficiency in one of the enzymes involved in glycosaminoglycan (GAG) catabolism. Over time, GAGs accumulate in cells and tissues causing progressive damage, a variety of multi-organ clinical manifestations, and premature death. Ear, nose, and throat (ENT) disorders affect more than 90% of MPS patients and appear in the early stage of MPS; also reported are recurrent otitis media and persistent otitis media with effusion, macroglossia, adenotonsillar hypertrophy, nasal obstruction, obstructive sleep apnoea syndrome (OSAS), hearing loss, and progressive respiratory disorders. Undiagnosed MPS patients are frequently referred to otolaryngologists before the diagnosis of MPS is confirmed. Otolaryngologists thus have an early opportunity to recognize MPS and they can play an increasingly integral role in the multidisciplinary approach to the diagnosis and management of many children with MPS. The ENT commitment is therefore to suspect MPS when non-specific ENT pathologies are associated with repeated surgical treatments, unexplainable worsening of diseases despite correct treatment, and with signs, symptoms, and pathological conditions such as hepatomegaly, inguinal hernia, macrocephaly, macroglossia, coarse facial features, hydrocephalous, joint stiffness, bone deformities, valvular cardiomyopathy, carpal tunnel syndrome, and posture and visual disorders.